2007
DOI: 10.1007/s00417-007-0631-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonmydriatic screening for diabetic retinopathy by ultra-widefield scanning laser ophthalmoscopy (Optomap)

Abstract: The Optomap Panoramic200 nonmydriatic images are of sufficient quality to assess DR and CSME validly and therefore fulfill the basic requirements for telescreening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 19 publications
2
70
0
Order By: Relevance
“…Effective axial line rate with 6x averaging is 1.1 MHz, still higher than the raw speed demonstrated with any non-FMDL light source. The en-face image also shows ciliary shadowing, a typical problem encountered in wide-field retinal imaging [78].…”
Section: 7 Mhz Dual-spot Imaging: Fdml Without Dispersion Compensationmentioning
confidence: 92%
“…Effective axial line rate with 6x averaging is 1.1 MHz, still higher than the raw speed demonstrated with any non-FMDL light source. The en-face image also shows ciliary shadowing, a typical problem encountered in wide-field retinal imaging [78].…”
Section: 7 Mhz Dual-spot Imaging: Fdml Without Dispersion Compensationmentioning
confidence: 92%
“…7 Our first observation was that although all ultra wide-angle images were gradable, there were nine conventional images that fell short of grading standards, predominantly due to media opacities and technical difficulties with positioning the patient for long enough to take gradable images. As lasers are much less susceptible to any media opacities 18,19 and they outperform even very high resolution digital images in terms of sharpness and contrast, 20 the better image quality is perhaps not surprising. However, it must be acknowledged that new graders must learn to appreciate artifacts related to the broad depth of focus of this device, such as the presence of eyelids, eyelashes, floaters (eg, see Supplementary Figure 1), the optics and the haptics of the intraocular lens or lens opacities.…”
mentioning
confidence: 99%
“…The potential for use of UWF imaging, particularly UWF FA, for enhancing diagnosis and treatment in DR has been demonstrated [23]. Several studies compared UWF pseudocolor images with conventional fundus photographs in the screening of DR [24][25][26][27]. Wilson et al [26] reported 83.6% sensitivity for UWF images versus 82.9% for digital photography in identifying DR. Silva et al [25] found that UWF matched 7 standard grading of severity in 80% of eyes and was within 1 level in 94.5% of eyes.…”
Section: Clinical Applications Of Ultra-widefield Imaging Diabetic Rementioning
confidence: 99%